Model for Securing Muhammadiyah Land Assets that Do Not Have Rights in North Sumatra Province - Ramadhani, Rahmat; Lubis, Ummi Salamah (Universitas Muhammadiyah Sumatera Utara, 2024)
This research aims to find a model for securing land assets of the Muhammadiyah Association in Prov. North Sumatera that has not yet been certified, especially for land that is controlled without a legal basis or whose legal basis has been lost, in an effort to prevent ownership disputes so that legal certainty can be secured, protected, and guaranteed. The research method used uses a type of normative legal research. Norms, rules, and legal principles related to the objectives of this research will be obtained from secondary data sources, including primary, secondary, and tertiary legal materials, which will be collected by means of library research and then processed and analyzed qualitatively using a qualitative approach. legislation (statute approach). The results of the research show that the factors inhibiting the security of Muhammadiyah Persyarikatan land assets in the North Sumatra Province area that do not have legal rights include technical and non-technical factors. Technical factors include lack of rights, historical actors who have died, land control by individuals, and funding factors. Meanwhile, non-technical factors include low public legal awareness, physical land plots not controlled or utilized optimally, and physical control of land plots located in protected areas to which rights cannot be attached. There are 3 asset security models that can be used to secure Muhammadiyah Persyarikatan land assets in the North Sumatra Province area that do not have a legal basis, namely the juridical data security model, the physical security model of land parcels, and the model of securing the status of land rights through land registration activities based on land law. which applies in Indonesia